EKSISTENSI BENDI DALAM PERSPEKTIF BUDAYA DI KOTA PADANG, PROVINSI SUMATERA BARAT - Vivindra, Riri Dwi; Syamsir, Syamsir; Nurman, Nurman (Humanus, 2015)
This study describes the competition between traditional and modern transport, the lack of awareness and knowledge of the community about ‘bendi’, bendi was considered harmful to the environment, the location of bendi wainting for passengers is unorganized that it is considered the cause of bottlenecks and constraints faced by the government in preserving bendi.. The research used descriptive qualitative approach. The informants were head of art and culture development in the Department of Tourism and Culture, head of traffic and public transport in the Department of Transportation, Communication and Information, bendi cabmem, bendi caretakers and the public or bendi passengers in Padang. Data were collected through interviews and document study. Data validity is tested using source triangulation techniques. Data was analysed by collection, reduction, data presentation and conclusions. Research findings portray that bendi is still existed in the cultural perspective, is still used in cultural events and serves as a means of cultural tourism in Padang. Bendi’s meaning and function are changed as seen through inhibiting factors that include internal and external factors. In order to overcome this problem, the government attempted to held festivals to provide information to the community or bendi owners and cooperate with the private sector in preserving bendi as cultural property in Padang city.Keywords: bendi, cultural property, transportation